An approach to conceptual and embodiment design within a new product development lifecycle framework. Issue 10 (18th May 2016) - Vila, Carlos; Albiñana, Juan Carlos
Abstract : The design of new innovative products is the result of an accurate and precise management of knowledge sources all over its life cycle, such as technology, market, competitors and suppliers. The work contributes with a framework that shows how the knowledge sources influence in the state-of-the-art and market needs so that they become opportunities for innovating products addressing the whole product life cycle. It provides a systematic path from the early generation of ideas to the production of a new product proposal. Through a deep analysis of previous research works of new product innovation life cycle development frameworks and linking it with knowledge management, strategic planning and scorecards, we came out with a structured contribution. The result considers the concurrent activities and its relationships all the way through the product life cycle that can help in creativity and innovation, combined with a process management proposal. Managing the sources of knowledge in highly dynamic markets and technologies is one of the major difficulties involved in innovative products design and development. The emerging knowledge from external sources is confronted with organisation internal knowledge and experience in order to achieve the first product correct.